2007
DOI: 10.1007/s00192-007-0411-z
|View full text |Cite
|
Sign up to set email alerts
|

The effect of spinal anaesthesia on urethral function

Abstract: This study was to assess the effect of spinal anaesthesia on urethral retro-resistance pressure (URP), cough pressures and tendency to leak. The population consisted of 32 women undergoing a tension-free vaginal tape (TVT) operation under a spinal anaesthetic. URP, cough pressures and an assessment of the degree of leak were performed before the spinal anaesthetic was placed. A standard anaesthetic technique was used, and measurements were repeated after the spinal anaesthetic was inserted. The degree of leak … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
1

Year Published

2008
2008
2022
2022

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 26 publications
0
5
1
Order By: Relevance
“…But this is not well tolerated by the patients, who require sedation or general anesthesia. In another study, the effect of spinal anesthesia on urethral function and cough pressure was evaluated; coughing under spinal anesthesia may not be as efficient as coughing without a spinal, and this resulted in cough-stress test being unable to reproduce preanesthetic conditions in women with a spinal anesthesia [19]. Similar to spinal anesthesia, epidural anesthesia can also cause weakness in cough pressures; however in our study, we saw no difference between the dexmedetomidine and epidural anesthesia groups.…”
Section: Discussioncontrasting
confidence: 69%
“…But this is not well tolerated by the patients, who require sedation or general anesthesia. In another study, the effect of spinal anesthesia on urethral function and cough pressure was evaluated; coughing under spinal anesthesia may not be as efficient as coughing without a spinal, and this resulted in cough-stress test being unable to reproduce preanesthetic conditions in women with a spinal anesthesia [19]. Similar to spinal anesthesia, epidural anesthesia can also cause weakness in cough pressures; however in our study, we saw no difference between the dexmedetomidine and epidural anesthesia groups.…”
Section: Discussioncontrasting
confidence: 69%
“…Adamiak et al found that the mean intra-abdominal cough pressure generated during spinal anesthesia was significantly lower than that of the women who coughed under LA [12]. In contrast, Duckett et al demonstrated that women were more likely to leak when coughing under spinal anesthesia than when awake preoperatively due to a fall in urethral resistance associated with spinal anesthesia [13]. As such, the anesthetic technique appears to strongly influence the use of the intraoperative cough test during the TVT.…”
Section: Discussionmentioning
confidence: 92%
“…When a cough test is used, more tension will need to be applied under spinal anaesthesia to achieve the same degree of leakage when compared to exactly the same technique with a local anaesthetic technique. However, different filling volumes were used to assess urethral function in this study compared to the previous work under spinal anaesthesia [7]. This might also have an effect on the URP results, although this should not alter the overall findings, as the patients acted as their own controls in both studies.…”
Section: Discussionmentioning
confidence: 88%
“…The operation can also be performed under regional anaesthesia [4,5]. Previous work assessing the effect of spinal anaesthesia on urethral function has demonstrated that cough pressures are not significantly reduced, but urethral relaxation causes an increased tendency to leak after the spinal anaesthetic [6,7]. Spinal anaesthesia alters the bladder neck position and urethral closure function, shortening the anatomical and functional urethral length and reducing the maximum urethral closure pressure and pressure transmission ratio in the urethra [6].…”
Section: Introductionmentioning
confidence: 99%